Foreign aid, green cities and buildings - Sandrine Kablan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper attempts, first, to assess foreign aid effectiveness in fostering green city procedures in developing countries. For this purpose, we rely on the following aid effectiveness criteria: national ownership; harmonization; alignment and mutual accountability; and results management. Our analysis shows that some programmes are effective and scalable. Secondly, using a GMM model, we try to link CO2 emissions from residential buildings as well as commercial and public services to foreign aid for renewable energy sources. Our results show that the effect of foreign aid is significant with a negative impact on CO2 emissions. The relationship is linear but also quadratic, indicating that there is a threshold before foreign aid can be effective in reducing CO2 emissions. Efforts of the international community for climate change mitigation through the promotion of green city procedures should be supported to reach appreciable levels so that foreign aid will help to promote green cities procedures and green building in developing countries.
Keywords: F64; O18; Q28; Q56; 330; climate change; climate finance; foreign aid; green cities and buildings; carbon emissions; Klimawandel; Nachhaltige Stadtentwicklung; Entwicklungshilfe; Entwicklungsländer